A memória escolar no virtual: Ambientes Virtuais de Aprendizagem (AVA), lugares da memória e da cultura escolar - Kessel, Zilda (2014)
The aim of this work is to study the Virtual Learning Environment (AVA) and to propose its understanding as a space that registers the school culture. The proposal uses conceptual contributions from History, Education and Information Science areas and seeks to demonstrate how the registers preserved in these environments are configured in a rich set of traces about the pedagogical doing. In them it is possible to identify not only the documents and proposals but also their execution, once they gather documents, students and teachers activities and final products. The everyday register of the school usually systematically disposed, emerges in the virtual space as a patrimony to be preserved, that can be read and studied ranging from the History of Education to studies on Curricula, besides enabling the reflexive work of both educators and students. Once accessible and as a reflection for educators ,researchers and students, it can become a place for memory